A Hybrid Genetic Algorithm for Selective Harmonic Elimination PWM AC/AC Converter Control - Dahidah, Mohamed S. A.; Rao, M. V. C. (SPRINGER, 2007)
This paper presents an optimal solution for eliminating pre-specified orders of harmonics from the output waveform of AC/AC converter. The main challenge of solving the associated nonlinear equations, which are transcendental in nature and therefore have multiple solutions, is the convergence and therefore an initial point selected considerably close to the exact solution is required. The paper discusses an efficient hybrid real coded genetic algorithm (HRCGA) that reduces significantly the computational burden resulting in a fast convergence. An objective function describing a measure of effectiveness of eliminating selected orders of harmonics, while controlling the fundamental is derived and a comparison of different operating points is reported. It is observed that the modulation index can reach unity value. The theoretical findings are verified through simulation results using the PSIM software package.